Temperature distribution analysis on diffusion bonded joints of Ti-6Al-4V with AISI 4140 medium carbon steel. (2020) - Sathish, T.; Dinesh Kumar, S.; Muthukumar, K.; Karthick, S.
Abstract: The major purpose of the present study is to investigate and compare the characteristics of dissimilar joining of Ti-6Al-4V with AISI 4140 Medium carbon steel using diffusion bonding process and analysis of the temperature distribution and stress intensity with the help of ANSYS software. For the diffusion bonding the joint quality is based on the process parameters like time, temperature and pressure maintained during the process. Diffusion bonding experiments for Ti-6Al-4V with AISI 4140 Medium carbon steel was carried out by varying the Pressure 5 MPa, 10 MPa and 15 Mpa, temperature 750 °C, 800 °C and 850 °C also time 60 min, 90 min and 120 min. The diffusion bonded joints of the Ti-6Al-4V with AISI 4140 Medium carbon steel created and temperature distribution were done by ANSYS.